Cognition in corticobasal syndrome and progressive supranuclear palsy: A review. Issue 5 (15th April 2014) - Burrell, James R.; Hodges, John R.; Rowe, James B.; Burn, David; Weintraub, Daniel; Robbins, Trevor
Abstract Corticobasal syndrome (CBS) and progressive supranuclear palsy (PSP) represent challenging neurodegenerative disorders for clinicians and nonclinical scientists alike. Although initially lumped together as "Parkinson's‐Plus" syndromes, CBS and PSP are clinically and pathologically distinct from Parkinson's disease. It is now clear that behavioral and cognitive changes are common in both syndromes and affect impact quality of life and carer burden considerably. We briefly review the clinical, pathological, and neuroradiological features of each syndrome, followed by more detailed descriptions of the behavioral and cognitive deficits encountered in CBS and PSP. Clinically and pathologically heterogeneous, CBS is characterized by a wide range of cognitive and behavioral disturbances. impairments in executive function and memory are common, but nonspecific. In contrast, deficits in language and visuospatial abilities appear to be more distinctive features of CBS; the relevance of specific patterns of impairment to the underlying histopathology, or prognosis, remains to be fully elucidated. As in CBS, behavioral and cognitive changes are almost universal in PSP, with a wide range of reported deficits. Apathy is very common, often paradoxically accompanied by impulsivity. Executive dysfunction is prominent, but memory and visuospatial deficits also occur. An emerging field is the study of social cognition, which appears impaired in both syndromes. As therapeutic strategies for neurodegenerative pathologies emerge, more specific diagnostic tools in CBS and PSP will be required. Careful clinicopathological correlation, and the development of biomarkers for specific histopathologies, will be important milestones on the road to effective treatments.